Early Surgical Decompression Ameliorates Dysfunction of Spinal Motor Neuron in Patients With Acute Traumatic Central Cord Syndrome: An Ambispective Cohort Analysis - Zheng, Chaojun; Yu, Qifeng; Shan, Xueli; Zhu, Yu; Lyu, Feizhou; Ma, Xiaosheng; Zhou, Shuyi; Jiang, Jianyuan (Spine (Philadelphia, Pa. 1976), 2020)
An ambispective cohort analysis. The aim of this study was to investigate the impact of early (≤2 weeks) versus delayed (>2 weeks) surgical intervention on the spinal motor neurons at and distal to injury site in acute traumatic central cord syndrome (ATCCS). Accumulating evidence demonstrated degeneration in distal lower motor neurons (LMNs) following spinal cord injury, and this secondary degeneration may exacerbate motor impairments and limit spontaneous motor recovery. However, few studies involved this pathological process in ATCCS. Motor unit number estimation (MUNE) was performed on both abductor pollicis brevis (APB) and extensor digitorum brevis (EDB) in 69 ATCCS patients (early vs. delayed surgical-treatment: 29 vs. 35) and 42 healthy subjects. All patients were assessed by American spinal injury association and Medical Research Council scales. These examinations and disabilities of arm, shoulder, and hand (c) questionnaire were administered approximately 21 months after operation in 65 of these patients. Preoperatively, MUNE values were lower in cervical-innervated muscles of ATCCS patients than in those of controls, and reduced motor units were observed in lumbosacral-innervated muscles in ATCCS patients with preoperative duration over 6 months (P < 0.05). Increased motor unit size without modification of MUNE values was found in delayed-surgical patients, whereas early-surgical patients mainly showed increased MUNE values in tested muscles between two assessments (P < 0.05). The postoperative follow-up analysis identified larger motor unit size and relatively fewer motor units in tested muscles, as well as higher DASH scores, in delayed-surgical patients than in early-surgical patients (P < 0.05). ATCCS has adverse downstream effects on the LMNs distal to injury site. Surgical intervention within 2 weeks after injury in ATCCS patients may be beneficial in ameliorating dysfunction of spinal motor neurons at and distal to injury site, reducing secondary motor neuron loss, and eventually improving neurologic outcomes. 3.